Comparative genomics reveals high biological diversity and specific adaptations in the industrially and medically important fungal genus Aspergillus - Vries, Ronald P. de; Riley, Robert; Wiebenga, Ad; Aguilar-Osorio, Guillermo; Amillis, Sotiris; Akemi Uchima, Cristiane; Anderluh, Gregor; Asaollahi, Mojtaba; Askin, Marion; Barry, Kerrie; Battaglia, Evy; Bayram, Ozgur; et al. (BioMed Central, 2017)
Background: The fungal genus Aspergillus is of critical importance to humankind. Species include those with industrial applications, important pathogens of humans, animals and crops, a source of potent carcinogenic contaminants of food, and an important genetic model. The genome sequences of eight aspergilli have already been explored to investigate aspects of fungal biology, raising questions about evolution and specialization within this genus.